KREATIVITAS SD TA’MIRUL ISLAM SURAKARTA DALAM PELATIHAN TARI - Hartanto Hartanto (Abdi Seni, 2020)
This article discusses creativity Elementary School Ta’mirul Islamic Surakarta in dance training. The goal of the training is grade 3.4, 5 and 6. The form of training is traditional dance creations and creativity in dance collaboration with the music of rabbana (Hadrah). Results of the training on traditional dance creations is the dance Soyong and dance Pangpung, while creativity produces motion of the song with the music of tambourines to MAPSI race. In the race, get the first winner District and Municipal level, and advance to the provincial level. This training is not to produce a perfect performance shape or focus on the mastery of the material as well, but it is more emphasized on the process, in case of emphasizing student involvement in tapping the creativity of the student’s ability  with freedom  and  flexibility  in managing  the  body and  expresses  it to  be  a  show. This  is supposed  to give  an  understanding of  basic  creativity, to  form  a creative  media,  to perform  the creative works and to document audio visual in order to be used as a reference in dance studying in elementary school.Keywords: creativity, dance, student of Elementary School, training.